2015
DOI: 10.1210/jc.2014-2674
|View full text |Cite
|
Sign up to set email alerts
|

Strong Effect of Pubertal Status on Metabolic Health in Obese Children: A Longitudinal Study

Abstract: MHO is a stable status in childhood obesity as long as pubertal status remains stable. Due to the strong association between puberty and MUO status, the concept of MHO is questionable, at least in pubertal children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
129
2
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(147 citation statements)
references
References 38 publications
11
129
2
5
Order By: Relevance
“…For instance, a recent study examining Chinese children and adolescents aged 6–18 years found that prevalence rates were 3.9 and 36.7% using 2 different MHO criteria defined by insulin resistance and cardiometabolic parameters, respectively [37]. Using the same MHO criteria as in the present study, a recently published German study on the effect of pubertal status revealed that a large proportion of obese children (49.3%) exhibited a MHO status [38]. It is likely that the high variability in reported MHO prevalence could be explained by the lack of a standard definition of MHO, specific cutoff values, small sample sizes, different age ranges, as well as behavioral differences between populations [39-41].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…For instance, a recent study examining Chinese children and adolescents aged 6–18 years found that prevalence rates were 3.9 and 36.7% using 2 different MHO criteria defined by insulin resistance and cardiometabolic parameters, respectively [37]. Using the same MHO criteria as in the present study, a recently published German study on the effect of pubertal status revealed that a large proportion of obese children (49.3%) exhibited a MHO status [38]. It is likely that the high variability in reported MHO prevalence could be explained by the lack of a standard definition of MHO, specific cutoff values, small sample sizes, different age ranges, as well as behavioral differences between populations [39-41].…”
Section: Discussionmentioning
confidence: 57%
“…Reinehr et al [38] showed that entering puberty doubles the risk of switching from MHO to MUO. The difference between pubertal stage and cardiometabolic alterations may be attributable to the physiological changes of body composition and the influence of sex hormones during puberty development [51].…”
Section: Discussionmentioning
confidence: 99%
“…However, even in childhood, BMI has been shown to be associated with cardiovascular risk factors similarly as directly determined fat mass (43). A strong association between puberty and MUO status has been found (44). Due to the initial design of COPAT project from which our cohorts were recruited we do not have data on pubertal stage being unable to analyze its impact on health risk.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, overweight and obese children enter puberty usually earlier than thin or normal weight children [57, 58]. As BP increases with puberty [59, 60] and early puberty has shown to be a risk factor for later high BP [57], this may have also contributed to higher BP in overweight/obese children. Also, inflammatory cytokines and adipocytokines from adipose tissue in overweight and obese subjects were shown to increase blood pressure [61, 62] such that obesity-related effects on BP may have overlaid the BP lowering effects of n-3 PUFA observed in thin/normal weight children.…”
Section: Discussionmentioning
confidence: 99%